2023
DOI: 10.1136/bmjopen-2022-066030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ED-based transitional care interventions by healthcare professionals providing transitional care in the emergency department on clinical, process and service use outcomes: a systematic review

Abstract: ObjectiveSuboptimal transitional care (ie, needs assessment and coordination of follow-up care) in the emergency department (ED) is an important cause of ED revisits and hospital admissions and may potentially harm patients, especially frail older adults. We aimed to systematically review the effect of ED-based interventions by health professionals who are dedicated to providing transitional care to older adults.DesignSystematic review.MeasurementsWe searched five biomedical databases for published (quasi)expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This study is consistent with a previous finding that ED-based transitional care interventions by healthcare professionals were associated with a significant decrease in ED visits. 18 We promoted coordination and continuity of care during the transition between providers, patients and families, and a personalized medical action plan was created via mobile application. A COPD pamphlet that explains how to use the green/yellow/red selfassessment and monitoring to monitor the early indications of an imminent exacerbation was given to family caregivers of OAW-COPD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is consistent with a previous finding that ED-based transitional care interventions by healthcare professionals were associated with a significant decrease in ED visits. 18 We promoted coordination and continuity of care during the transition between providers, patients and families, and a personalized medical action plan was created via mobile application. A COPD pamphlet that explains how to use the green/yellow/red selfassessment and monitoring to monitor the early indications of an imminent exacerbation was given to family caregivers of OAW-COPD.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that studying the effectiveness of transitional care interventions can help optimize the transition of care for older ED patients and reduce the risk of costly and potentially harmful readmissions for this population. 18 In addition, symptom management programs significantly reduce dyspnea symptoms and anxiety among OAW-COPD. 19…”
Section: Vol 28 Nomentioning
confidence: 99%
See 2 more Smart Citations
“…Transitional care encompasses a broad range of services including comprehensive assessment, patient and family education, staff handover and communication, medication reconciliation, and development of a care management plan [12,13]. Two types of ED-based transitional care interventions were identified in a recent systematic review [14]. The first intervention type (individual needs assessment) comprised a structured comprehensive assessment of patient's individual needs and care and addressing these through site specific or outpatient resources.…”
Section: Introductionmentioning
confidence: 99%